In silico Prediction, in vitro Antibacterial Spectrum, and Physicochemical Properties of a Putative Bacteriocin Produced by Lactobacillus rhamnosus Strain L156.4 - Oliveira, Letícia de C.; Silveira, Aline M. M.; Monteiro, Andréa de S.; dos Santos, Vera L.; Nicoli, Jacques R.; Azevedo, Vasco A. de C.; Soares, Siomar de C.; Dias-Souza, Marcus V.; Nardi, Regina M. D. (Frontiers in Microbiology, 2017)
A bacteriocinogenic Lactobacillus rhamnosus L156.4 isolated from the feces of NIH mice was identified by sequencing of rRNA 16S and MALDI-TOF mass spectrometry. The whole genome was sequenced using Illumina, annotated in PGAAP and RAST server, and deposited. The prediction of conserved genes associated to bacteriocin synthesis was performed using BAGEL3, what led to the finding of an open reading frame (ORF) that shows homology with the prebacteriocin gene of L. rhamnosus GG (ATCC 53103) containing a conserved protein motif associated to the structural gene of Enterocin A superfamily. Sequences related to the prebacteriocin, immunity protein, ABC transporter proteins and regulatory genes with 100% identity to those of L. rhamnosus HN001 were also found. Antagonistic substances, which included organic acids and a putative bacteriocin produced by L. rhamnosus L156.4, presented a wide antimicrobial activity spectrum against Gram-negative and Gram-positive bacteria, including human and foodborne pathogens. The antagonistic substances were produced during bacterial logarithmic phase and were sensitive to proteolytic enzymes, heat stable and maintained their activity in a pH ranging from 3 to 9 against Lactobacillus fermentum, which was used as an indicator strain. After partial purification from cell-free supernatant by salt precipitation, the putative bacteriocin migrated as a diffuse band of approximately 1.0 - 3.0 kDa in SDS-PAGE. More studies are being conducted for exploring its use in the food industry for controlling bacterial growth or for probiotic applications.